THE EFFECT OF QUALITY MANAGEMENT, ORGANIZATIONAL CULTURE AND PROFESSIONALISM - Sudirwan, Joseph (Journal of Education Research in Administration and Management (JERAM), 2017)
This research was aimed to determine the effect of quality management, organizational culture, and professionalism against the lecturer’s caring. The quantitative research approach using a survey method and technique of path analysis. The population was the lecturer of Bina Nusantara University and 166 lecturers were taken as samples and selected using stratified random sampling.  The result of data analysis showed that quality management, organizational culture, and professionalism have a direct positive effect on the lecturer’s caring. Quality management and organizational culture, have a direct positive effect on the professionalism and quality management, has a direct positive effect on the organizational culture. Therefore, to improve lecturer’s caring of Bina Nusantara University, the quality management, organizational culture, and professionalism should be improved.   Keywords: Quality management, organizational culture, professionalism, and lecturer’s                      caring.